The effect of cold atmospheric plasma (NO) alone and in combination with NPH insulin on the full-thickness excisional wound healing in a diabetic rat model - Curukoglu, A; Gungor, G. C. A; Akan, G; Kukner, A; Ogutcu, G; Kalaycı, M; Temizel, M; Ozgencil, F. E (Veterinární medicína, 2023)
This study was planned to investigate an alternative treatment modality in diabetic wound healing. In this experimental study, the efficacy of both cold atmospheric plasma/nitric oxide (NO) and NPH insulin ointment, recently known to have beneficial effects on wound healing, was investigated in diabetic wound healing. Twenty-four (24) diabetic rats were divided into four groups DC, DI, DNO and DINO (diabetic control, diabetic insulin, diabetic nitric oxide, diabetic insulin + nitric oxide groups). No treatment was applied to the DC group, NPH insulin was applied to the DI group, CAP/NO was applied to the DNO group, and CAP/NO + NPH insulin was applied to the DINO group once daily for 14 days. The wound area reduction and the wound contraction rate were calculated on the basis of the tissue sections taken, and histopathological and genetic analyses were carried out. Compared to the control group, exogenous NO gas was found to be a potent antibacterial agent in the diabetic wound healing, causing a reduction in the wound area (P = 0.034), an increased contraction rate (P = 0.021), epithelialisation (P = 0.02), collagen organisation (P = 0.006) and a reduction in the number of inflammatory cells (P = 0.002). A significant increase in the expression of IL-8 mRNA was observed (P = 0.026). It was concluded that NPH insulin alone contributes to wound healing, but it is not necessary to use it together with exogenous NO gas.